KISAH NABI MŪSĀ DALAM SURAT AL-QAṢAṢ (STUDI PEMIKIRAN AL-ṢĀWĪ DALAM ḤĀSYIAH AL-ṢĀWĪ ‘ALĀ TAFSĪR AL-JALĀLAIN) - Khasanah, Amriah Nurul (Academic Journal of Islamic Principles and Philosophy, 2022)
This article discusses the thoughts of al-Ṣāwī in the story of Prophet Mūsāin the Surahof al-Qaṣaṣ. Al-Ṣāwī is a figure of Qur’an interpretation (Tafsīr) born in Egypt, and came from the Maliki school of the Khalwatiyyah Sufi sect. He composed Ḥāsyiyahal-Ṣāwī ‘alā Tafsīr al-Jalālainfrom the Tafsīr of Imām Jalāl al-Dīn al-Maḥallī and Imām Jalāl al-Dīn al-Suyūṭī who is different from him. The study of al-Ṣāwīrelated to the Surahof al-Qaṣaṣis interesting because he named it as the Surahof Mūsā. The results of this study concluded that the explanation of al-Ṣāwī in the story of Prophet Mūsā in Surahal-Qaṣaṣcovers the life of Prophet Mūsā from childhood to adulthood. It begins with the dream of Pharaoh who will be ruled by a baby who comes from the children of Israel until the Prophet Mūsā sovereign Pharaoh. Then the values ​​that can be learned from the story of Prophet Mūsā are the patience and obedience of the mother of Prophet Mūsā, the intelligence of Prophet Mūsā, trustworthy, tough, strong, mighty, gentle. and the struggle and persistence to deal with Pharaoh and his people.